ANALISIS RISIKO BISNIS DAN RISIKO KEUANGAN PERUSAHAAN KELUARGA SEKTOR INDUSTRI BARANG KONSUMSI - Subagio, David Kurniawan; Manalu, Sahala (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
Abstract.This study was conducted to prove whether the level of business risk and financial risk from family firm significant lower than the average of the consumer goods industry Listed in Indonesia Stock Exchange. This study uses secondary data, financial reports companies listed on the Stock Exchange in the period 2010-2014. Data was collected using documentation method. The sampling technique using purposive sampling method, the number of samples i this study were 8 family companies . The result showed that there no significant difference between DOL, DFL, DER, DAR, current ratio, quick ratio, cash ratio from family companies and average of consumer goods industry that Listed in Indonesia Stock Exchange in 2010-2014.Keywords : Business Risk, Financial Risk, Family FirmPENDAHULUANLatar Belakang MasalahPerusahaan keluarga merupakan perusahaan yang telah menguasai 80%-98% bisnis di dunia (PT. Bank Mandiri TBK, 2012). Biro Pusat Statistik mencatat, perusahaan keluarga Indonesia merupakan perusahaan swasta yang memiliki kontribusi yang besar terhadap PDB, yaitu mencapai 82,44% (PT. Bank Mandiri TBK, 2012). Hal ini membuktikan bahwa perusahaan keluarga merupakan perusahaan yang vital dan penting bagi perekonomian, dan terutama pada perekonomian Indonesia.Fenomena lain juga terjadi di Indonesia dimana